Digital Aesthetics in Kindergarten: Examples of Using Digital Media in Working with Children - Čolakov, Nevena D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The article discusses how and in which ways digital media can be integrated into working with preschool children from the perspective of visual pedagogy. The works of Pavlović Breneselović on digital technologies in kindergartens and the competencies educators need for working with digital media served as the theoretical framework for analysing the integration of digital media in early childhood. Starting from the principles of using digital technologies in kindergartens, derived from the theoretical framework of the ‘Foundations of the Curriculum’ concept (Pavlović Breneselović, 2021), our goal was to analyse the extent to which these principles are represented in two examples of digital media use described in this paper (research by Leung et al., 2020; Harwood, 2017). Using the same examples, we also attempted to answer whether and to what extent the nature of visual arts (the artistic and aesthetic context of play) is preserved.